2017
DOI: 10.15171/apb.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Complex Technique for Superior Bioavailability of Phytoconstituents

Abstract: Phytoconstituents have been utilized as medicines for thousands of years, yet their application is limited owing to major hurdles like deficit lipid solubility, large molecular size and degradation in the gastric environment of gut. Recently, phospholipid-complex technique has unveiled in addressing these stumbling blocks either by enhancing the solubilizing capacity or its potentiating ability to pass through the biological membranes and it also protects the active herbal components from degradation. Hence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…This type of interaction leaves the fatty acid chains free, so they can further move to encapsulate the polar portion of the complex forming a lipophilic surface [30]. Thus, phytosomes have the potential to enhance the oral bioavailability of plant-derived bioactives [31]. Phytosome use in transdermal drug delivery has also been reported [32].…”
Section: Introductionmentioning
confidence: 99%
“…This type of interaction leaves the fatty acid chains free, so they can further move to encapsulate the polar portion of the complex forming a lipophilic surface [30]. Thus, phytosomes have the potential to enhance the oral bioavailability of plant-derived bioactives [31]. Phytosome use in transdermal drug delivery has also been reported [32].…”
Section: Introductionmentioning
confidence: 99%
“…The plant extracts or its monomers are firmly bound to phosphatidylcholine, a main constituent of phospholipids, resulting in a lipid compatible molecular complex. Phytosomes can significantly improve the pharmacokinetic and pharmacodynamic profiles of phytomedicines compared to the unmodified modalities [ 103 ]. Phytosomes are originally developed for handling the water-soluble phytomedicines with poor oral absorption due to their large molecular size and lack of lipophicity, but now not limited to water-soluble active compounds.…”
Section: Lipid Dispersion Techniquementioning
confidence: 99%
“…The in vivo studies showed that the liposomal formulation demonstrated a significant analgesic activity in mice. In recent years, phytosomes (phospholipid complexes) are also being widely used for oral drug delivery [ 103 ]. For example, Freag et al developed self-assembled phytosomal nanocarriers for improving the solubility and oral bioavailability of celastrol [ 151 ], and Telange et al developed apigenin-loaded phytosomes to improve the drug’s aqueous solubility, dissolution, in vivo bioavailability, and antioxidant activity [ 106 ].…”
Section: Lipid Dispersion Techniquementioning
confidence: 99%
“…As illustrated in Table 4, phytosome carrier can also deliver bioactive compounds, both lipophilic and hydrophilic, in order to enhance oral bioavailability (Lu et al, 2018). Phytosomes are a durable complexes, with a simple manufacturing process (Gnananath et al, 2017). Complexing reaction of milk phospholipids and encapsulate (molecular ratio 1-5) was realized in either ethanolic or methanolic solution of 55°C.…”
Section: Phytosomesmentioning
confidence: 99%